2015
DOI: 10.1007/s12288-015-0542-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea in Sickle Cell Disease: Our Experience in Western India

Abstract: Sickle cell disease (SCD) is common in tribal belt of Gujarat, but not addressed effectively as it should be with effective use of Hydroxyurea, supportive care and counseling. In our single centre study of 70 patients of SCD who were only on Folic acid and Blood transfusion support, were analyzed and followed up for 1 year in terms of their clinical symptoms, Blood transfusion requirement, laboratory parameters before and after Hydroxyurea therapy. We found statistically significant improvement in clinical sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 21 publications
4
16
0
Order By: Relevance
“…It is well known that HU increases HbF and total Hb level [1,10]. Similar to studies by Pondugala et al [13] and Deshpande et al [14], we observed a statistically significant increase in the total Hb level with HU therapy. Raised Hb level after starting HU therapy may be due to reduction in RBC destruction due to hemolysis.…”
Section: Discussionsupporting
confidence: 91%
“…It is well known that HU increases HbF and total Hb level [1,10]. Similar to studies by Pondugala et al [13] and Deshpande et al [14], we observed a statistically significant increase in the total Hb level with HU therapy. Raised Hb level after starting HU therapy may be due to reduction in RBC destruction due to hemolysis.…”
Section: Discussionsupporting
confidence: 91%
“…There is now over 30 years of published evidence proving the efficacy of hydroxyurea in the treatment of both adults and children with SCD in the United States, Europe, Brazil, and India. [40][41][42][43][44][45] The results of the pivotal randomized trial of hydroxyurea in adults (MSH) showed benefits in the reduction of the number of vasoocclusive pain episodes, acute chest syndrome, requirement for blood transfusions, and hospitalizations. 41,42 Another placebocontrolled trial of hydroxyurea therapy in infants and toddlers with SCD (BABY-HUG) produced similar results.…”
Section: Hydroxyurea Therapymentioning
confidence: 99%
“…[27][28][29]45,[57][58][59][60][61][62] For example, hydroxyurea use has been shown to reduce the vasoocclusive crises, stroke, infections, malaria, transfusions, and death in children with SCD, warranting the need for wider access to this treatment. 29,[59][60][61][62] Hydroxyurea treatment has been shown to be feasible, safe, and effective in children with SCD living in India 63 and in sub-Saharan Africa. 29,59,64,65 In this manuscript, we describe the design, development, manufacturing, and clinical testing of a novel point-of-care hemoglobin test, HemeChip.…”
Section: Introductionmentioning
confidence: 99%